Matrix-assisted laser desorption/ionization mass spectrometry imaging for the analysis of pro-and anti-inflammatory macrophages and murine and human atherosclerotic tissue samples - Khamehgir-Silz, Pegah; Justus Liebig University Giessen (My University, 2025)
The primary objective of this dissertation is the use of Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging (MALDI MSI) for the visualization and characterization of pro- and anti-inflammatory macrophages as well as atherosclerotic plaques in murine models and human tissue samples. In the first publication, a comprehensive methodology was developed to distinguish pro- and anti-inflammatory human macrophages using MALDI-MSI, RT-qPCR, and FACS. The macrophage subtypes M1, M2a, and M2c could be successfully distinguished based on expression profiles of marker genes using RT-qPCR and FACS. A comprehensive working protocol for the preparation, measurement and data analysis for MALDI-MSI was developed and established. The method identified subtype-specific markers and showed good reproducibility in three biological replicates based on principal component analysis (PCA) and hierarchical cluster analysis (HCA). The heterogeneity of cells from different donors became apparent when the number of biological replicates was increased from 3 to 6. Due to the biological variability of cells derived from various donors, identifying universal markers for in-vitro stimulated human macrophages posed challenges. In the second publication, lipid markers associated with plaque formation and development in ApoE-/- mice were successfully identified, and their presence in human atherosclerotic tissue was investigated. The determined results clearly showed differences in the lipid profile of the older ApoE-/-mice compared to the wild-type mice. Thirty-one compounds that were exclusively detected in the ApoE-/- mice were identified as markers. The results of the human atherosclerotic tissue samples showed significantly different lipid profiles, making it difficult to identify universal markers. However, in particular tissue samples, it was possible to detect markers identified in the murine plaques tissue samples. These findings demonstrate a patient-specific lipid profile and support previous findings suggesting that clinically significant atherosclerotic plaques contain a variable mixture of lipids. The detected variance in lipid compositions could be related to different stages of atherosclerosis progression and factors such as diet, lifestyle and medication. These findings highlight the necessity of considering unique patient characteristics, such as medication history, when analyzing lipid profiles in atherosclerosis studies. Overall, this PhD thesis contributes to our understanding of the lipid composition in atherosclerotic plaques and highlights the potential of MALDI MSI as a valuable, powerful technique for studying macrophages and atherosclerotic plaques in murine models and human samples. The findings provide a useful basis for future research approaches and may aid in developing novel diagnostic and therapeutic strategies for cardiovascular disease.
Keywords: ddc:540